Associations between domains of health-related quality of life and comorbid emotional and behavioral problems in youth with autism spectrum disorder - Menezes, Michelle (Res Autism Spectr Disord, 2021)
BACKGROUND: Health-related quality of life (HRQoL) can be used as a measure of the impact of a particular disorder on one’s daily functioning. Previous studies have found that comorbid psychiatric disorders in children and adolescents with autism spectrum disorder (ASD) are associated with poorer HRQoL than ASD alone. Less is known about potential associations between specific symptoms of comorbid psychopathology (i.e., emotional and behavioral problems) and domains of functioning or HRQoL in youth with ASD. METHOD: Participants were 470 children with ASD 2–14 years old recruited from one of three sites. Hierarchical multiple regressions were conducted with Pediatric Quality of Life Inventory 4.0 (PedsQL; Varni et al., 2001) HRQoL domains of physical functioning, emotional functioning, school functioning, and social functioning as the dependent variables. Covariates were entered at step 1, followed by the independent variables of interest at step 2: irritability, social withdrawal, stereotypic behavior, hyperactivity/noncompliance, and inappropriate speech. RESULTS: The study found that increased irritability was associated with poorer emotional and physical functioning and that greater social withdrawal was associated with worse social functioning. Furthermore, findings showed that more hyperactivity/noncompliance was associated with worse school functioning. CONCLUSIONS: Results demonstrated that certain emotional and behavioral symptoms are differentially associated with domains of HRQoL. This indicates that comorbid emotional and behavioral problems should be considered when measuring HRQoL in children with ASD. It also suggests that treating comorbid emotional/behavioral problems could improve HRQoL and functioning in certain domains for this population.